Tropical Orb Weaver Spider, Eriophora ravilla (C. L. Koch) (Arachnida: Araneae: Araneidae) - Glavis B. Edwards (EDIS, 2005)
Among the several large orb weavers occurring in Florida is Eriophora ravilla (C.L. Koch). Unlike similar large spiders of the genus Neoscona (Edwards 1984), E. ravilla is not a conspicuous member of the diurnal fauna during its adult stage. Nevertheless, nursery inspectors regularly encounter specimens of this species and submit them to the Division of Plant Industry for identification. Bites of this species are not known to cause serious effects to humans. This document is EENY-291 (originally published as DPI Entomology Circular 286), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.